THE IMPACT OF FOSTERING SPEAKING SKILLS THROUGH NOICE APPLICATION : A SYSTEMATICAL LITERATURE REVIEW - Evan Kurniawan; Velina Cindy Sagita; Siti Aulia Sintia; Naf’an Tarihoran (Jurnal Intelek Insan Cendikia, 2025)
This study investigates the effectiveness of the Noice application as a digital audio platform for improving EFL learners’ speaking skills through a PRISMA-based Systematic Literature Review (SLR). From 207 identified articles, ten studies met the criteria for analysis. The findings show that Noice provides authentic and repeated English input through podcasts, audio stories, and conversational content that support the development of fluency, pronunciation, vocabulary, and oral organization. Its flexible and non-visual format creates a low-anxiety environment that increases learners’ confidence and encourages autonomous learning, allowing students to adjust practice intensity and revisit materials as needed. Noice is also more aligned with the preferences of digital-native learners and supports principles of Communicative Language Teaching, digital storytelling, and flipped learning. Overall, Noice demonstrates strong potential as an innovative supplementary tool for enhancing EFL speaking skills by offering rich exposure, promoting independence, and creating an engaging learning experience